Performance parameters of a liquid filled ionization chamber array. Issue 8 (31st July 2013) - Poppe, B.; Stelljes, T. S.; Looe, H. K.; Chofor, N.; Harder, D.; Willborn, K.
Abstract : Purpose: : In this work, the properties of the two‐dimensional liquid filled ionization chamber array Octavius 1000SRS (PTW‐Freiburg, Germany) for use in clinical photon‐beam dosimetry are investigated. Methods: : Measurements were carried out at an Elekta Synergy and Siemens Primus accelerator. For measurements of stability, linearity, and saturation effects of the 1000SRS array a Semiflex 31013 ionization chamber (PTW‐Freiburg, Germany) was used as a reference. The effective point of measurement was determined by TPR measurements of the array in comparison with a Roos chamber (type 31004, PTW‐Freiburg, Germany). The response of the array with varying field size and depth of measurement was evaluated using a Semiflex 31010 ionization chamber as a reference. Output factor measurements were carried out with a Semiflex 31010 ionization chamber, a diode (type 60012, PTW‐Freiburg, Germany), and the detector array under investigation. The dose response function for a single detector of the array was determined by measuring 1 cm wide slit‐beam dose profiles and comparing them against diode‐measured profiles. Theoretical aspects of the low pass properties and of the sampling frequency of the detector array were evaluated. Dose profiles measured with the array and the diode detector were compared, and an intensity modulated radiation therapy (IMRT) field was verified using the Gamma‐Index method and the visualization of line dose profiles. Results: : The array showed a short and long term stability better than 0.1% and 0.2%, respectively. Fluctuations in linearity were found to be within ±0.2% for the vendor specified dose range. Saturation effects were found to be similar to those reported in other studies for liquid‐filled ionization chambers. The detector's relative response varied with field size and depth of measurement, showing a small energy dependence accounting for maximum signal deviations of ±2.6% from the reference condition for the setup used. The σ‐values of the Gaussian dose response function for a single detector of the array were found to be (0.72 ± 0.25) mm at 6 MV and (0.74 ± 0.25) mm at 15 MV and the corresponding low pass cutoff frequencies are 0.22 and 0.21 mm −1, respectively. For the inner 5 × 5 cm 2 region and the outer 11 × 11 cm 2 region of the array the Nyquist theorem is fulfilled for maximum sampling frequencies of 0.2 and 0.1 mm −1, respectively. An IMRT field verification with a Gamma‐Index analysis yielded a passing rate of 95.2% for a 3 mm/3% criterion with a TPS calculation as reference. Conclusions: : This study shows the applicability of the Octavius 1000SRS in modern dosimetry. Output factor and dose profile measurements illustrated the applicability of the array in small field and stereotactic dosimetry. The high spatial resolution ensures adequate measurements of dose profiles in regular and intensity modulated photon‐beam fields.